Team efficacy profiles: Congruence predicts objective performance of athlete pairs - Habeeb, C. M.; Stephen, S. A.; Eklund, R. C. (Journal of Sport & Exercise Psychology, 2024)
Efficacy beliefs targeting personal (self-efficacy), teammates` (other-efficacy), and conjoint (collective efficacy) abilities are each associated with performance of athlete pairs. The purpose of this study was to examine (a) congruence/incongruence of efficacy beliefs between athletes in a pair as a predictor of quality of individual and team performance and (b) quality of performance relative to efficacy congruence at high, moderate, and low levels of efficacy. Eighty-two cheerleading pairs, composed of one base and one flyer, completed questionnaires assessing self-, other, and collective efficacy prior to a national collegiate competition. Individual and team performances were assessed using objective criteria. Polynomial regression analyses indicated that team performance was predicted by congruence of (a) both athletes` collective efficacy beliefs and (b) base self-efficacy and flyer other efficacy. Findings supported that congruence at moderate to high levels of efficacy was associated with better performance relative to incongruent efficacy beliefs across the two athletes.